2019
DOI: 10.17116/profmed20192202157
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for vitamin D deficiency in the inhabitants of the Russian Arctic according to rs9939609 polymorphism

Abstract: The relationship between FTO rs9939609 polymorphism and 25(OH)D (25-hydroxycholecalciferol) deficiency was studied among the population of the Arctic Zone of the Russian Federation (Yamal-Nenets Autonomous Area). A total of 175 people, including 135 women and 40 men, aged 19 to 75 years were examined. Among all the examinees, the indigenous population of the Arctic Zone constituted 81%, the Nenets of whom made up 98%. The studies of vitamin D concentrations in the indigenous population living in the Arctic Zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Data from other authors on this issue are also extremely contradictory as well. For example, studies in China and Russia have demonstrated that lower 25(OH)D levels are associated with the ff genotype rs2228570 (FokI T > C) [ 64 , 65 ], while deficiency in the Syrian population was associated with the FF genotype [ 66 ]. Three more research teams (namely, two from India and one from Greece) showed no relationship between genetic variations in rs2228570 and 25(OH)D concentrations [ 63 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from other authors on this issue are also extremely contradictory as well. For example, studies in China and Russia have demonstrated that lower 25(OH)D levels are associated with the ff genotype rs2228570 (FokI T > C) [ 64 , 65 ], while deficiency in the Syrian population was associated with the FF genotype [ 66 ]. Three more research teams (namely, two from India and one from Greece) showed no relationship between genetic variations in rs2228570 and 25(OH)D concentrations [ 63 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ген FTO, связанный с жировой массой и ожирением, кодирует альфа-кетоглутаратзависимую диоксигеназу, которая посредством метилирования ДНК и РНК регулирует транскрипцию и трансляцию [8]. Хотя молекулярный механизм участия этого гена в формировании ожирения до конца не понятен, полиморфизмы этого гена тесно связаны с риском развития избыточной массы тела и ожирения [8,13]. Наиболее однозначно с риском развития ожирения ассоциирован полиморфизм rs9939609, местоположение 16q12.2.…”
unclassified
“…(2019), характер и степень ассоциации полиморфизма генов FTO, а также частота встречаемости аллеля А существенно обусловлены расовоэтническим происхождением респондентов [14]. О подтверждении связи варианта rs9939609 гена FTO с риском ожирения были получены данные в различных популяциях, в том числе в Западной [15] и Восточной Азии [11,13], Южной Америке [3,16], а также в различных регионах России [5,10,[17][18][19]. Вместе с тем S. Doaei et al (2019) [20], объединив скорректированные коэффициенты шансов (OR) по восьми подходящим по критериям исследованиям типа «случай -контроль», установили, что ассоциация между полиморфизмом rs9939506 и ожирением оставалась значимой в европейской подгруппе (OR = 1,68 [1,2-2,36]), но не в азиатской подгруппе (OR = 0,94 [0,81-1,10]; OR = 0,95 [0,80-1,14]; OR = 2,31 [0,96-5,58]).…”
unclassified
“…According to А.К. Baturin with colleagues (2019), the essence and intensity of the association between FTO gene polymorphisms as well as the A allele frequency are largely determined by respondents' race and ethnic group [14]. The aforementioned association between the rs9939609 FTO polymorphism and a risk of obesity has been evidenced by data obtained on various populations including the West [15] and East Asia [11,13], South America [3,16], as well as in different regions in Russia [5,10,[17][18][19].…”
mentioning
confidence: 99%
“…We used TaqMan probes complimentary to DNA polymorphisms and relevant reagents (Syntol, Russia). Amplification was accomplished with a CFX96 Real Time System (Bio-Rad, USA) in real time [5,10,14].…”
mentioning
confidence: 99%